Efektivas Ta’zir dalam Meningkatkan Disiplin Santri di Pondok Pesantren At-Tauhid Kampoeng Tauhid Sriwijaya Ogan Ilir - Ari Alhadi; Dwi Noviani; Ardeni (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2022)
Discipline is a person's attitude of self-control in order to be able to distinguish between what is right and what is wrong. So that in the long term it is expected to foster responsible behavior. Discipline is also very much needed in various educational institutions, one of which is Islamic boarding schools. Ta'zir is one part of the method for disciplining students. Besides that, ta'zir aims to improve the quality of discipline of students in Islamic boarding schools. This researcher examines the effectiveness of ta'zir with student discipline at the At-Tauhid Islamic Boarding School. The results of research at the At-Tauhid Islamic Boarding School on the effectiveness of ta'zir improve the discipline of obeying the rules.